2022
DOI: 10.1021/acs.energyfuels.2c01199
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Structural Damage to Coal Treated by a High-Voltage Electric Pulse Discharge in Water

Abstract: High-voltage electric pulse (HVEP) technology has been gradually adopted as an effective method in the drainage and utilization of coalbed methane (CBM) in low-permeability coal reservoirs. An experimental device was established to study the structural variation characteristics of bituminous coal samples treated by an HVEP. The structure parameters of coal samples before and after the HVEP treatment were measured using a scanning electron microscope and low-temperature nitrogen adsorption. Additionally, the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…After being treated, it promotes the expansion and penetration of micro and macro pores and fractures in coal, which improves the permeability of the coal seam and verifies the effectiveness of the CSW on the coal fracturing (Li et al 2022a;Yan et al 2019). Chen et al ( 2012) conducted an experiment of pulse discharge in water in a rectangular tank, and the experimental device is shown in Fig.…”
Section: Experiments On Coal Fracturing By Shock Wave Under Different...mentioning
confidence: 86%
See 1 more Smart Citation
“…After being treated, it promotes the expansion and penetration of micro and macro pores and fractures in coal, which improves the permeability of the coal seam and verifies the effectiveness of the CSW on the coal fracturing (Li et al 2022a;Yan et al 2019). Chen et al ( 2012) conducted an experiment of pulse discharge in water in a rectangular tank, and the experimental device is shown in Fig.…”
Section: Experiments On Coal Fracturing By Shock Wave Under Different...mentioning
confidence: 86%
“…8a, the Institute of Electrical Industry of the Chinese Academy of Sciences adopted the pulse discharge fracturing experiment of the specimen in the pressure kettle to apply the stress to the coal rock specimen, so as to better simulate the underground engineering implementation conditions of the borehole. Researchers in France have developed a set of experimental device for pulse discharge fracturing and permeability enhancement, in which the principle stress is applied to the top hydraulic cylinder and confining pressure is loaded with lateral constraints (Li 2011;Chen et al 2012), as shown in Fig. 8b.…”
Section: Experimental Devicementioning
confidence: 99%
“…The CSW fracturing coal is preliminarily explored. Compared with the traditional hydraulic fracturing method, the CSW technology is water-saving with high efficiency, good fracture connectivity, complex fracture network, and repeatable fracturing [18,19] . At present, the effectiveness of CSW in fracturing coal has been verified by experiments [20] .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the effectiveness of CSW in fracturing coal has been verified by experiments [20] . Many scholars have studied the initiation and propagation mechanism of coal cracks under the impact load [21] . It is found that the initiation coal cracks follows the maximum tensile stress criterion [22] , and the damage propagation in coal is related to the times of impact [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the desired effect, grouting reinforcement technology is often combined with fracturing, antireflection and other technologies. In recent years, electric pulse technology has gradually been popularized and applied with increasing permeability [14][15][16][17]. The principle of electric pulse antireflection is that the capacitor stores a certain high voltage and uses two electrodes placed in water to generate pulse discharge in a very short time.…”
Section: Introductionmentioning
confidence: 99%